Systematic Parameter Optimization for Electrospraying of PVA and PVP Aqueous Solutions - Vivas-Torrez, Wilbert Arturo; López-Calderón, Héctor D.; Laguna-Camacho, Juan Rodrigo; Martínez-López, Andrea Guadalupe; Velázquez-Martínez, Víctor; Calderón-Sánchez, Javier; López-Calderón, Jesús Enrique; Calderón-Ramón, Celia (Journal of Research Updates in Polymer Science, 2025)
This study systematically optimizes the key electrospraying parameters—flow rate, applied voltage, and nozzle-collector distance—for generating polymer micro/nanospheres from aqueous solutions of polyvinyl alcohol (PVA) and polyvinylpyrrolidone (PVP). Solutions at concentrations of 10%–15% w/v were characterized by conductivity measurements, revealing a significant solvent-dependent effect (450 µS/m–590 µS/m for water vs. 44 µS/m–56 µS/m for ethanol). Through iterative testing, two distinct sets of optimal parameters were identified: 10% PVA at 20 µL/h, 25 kV, and 12 cm distance, and 15% PVP at 10 µL/h, 30 kV, and 14 cm distance. Statistical analysis (ANOVA) confirmed a significant interaction between polymer type and concentration on solution conductivity (p< 0.05). Strict environmental control (≤24 °C, ≤44% RH) was essential for process stability. Optical microscopy confirmed the formation of structures under the optimized conditions. This work establishes a reproducible parametric framework for the electrospraying of PVA and PVP, providing a critical foundation for the subsequent development of functional polymer particles for potential applications in catalysis and drug delivery.